MANAJEMEN ISTANO BASA PAGARUYUNG - Fani Ratny Pasaribu (LPPM Universitas Bina Sarana Informatika, 2019)
ABSTRACTManagement of the Istano Basa Pagaruyung management in Batusangkar is very important to consider in its implementation, because it must be approved that Istano's administrative management is not carried out properly so that it will be a big problem for the City of Batusangkar. The question in this study is to find out the Istano Basa Pagaruyung management. Problems can be seen from the challenges that occur. The research method used is descriptive qualitative research with basic research in the form of case studies. Data collection techniques were carried out in the form of library studies and in-depth interviews. Based on research obtained from the management of Istano Basa Pagaruyung in Batusangkar, it has not run optimally. Because difficulties are still found in management, only a portion of it is of concern to the Regional Government regarding Istano's needs regarding the number of employees and the budget. The importance that occurs in the Istano environment. The government should pay special attention to the development of tourism objects. Taking Istano Pagaruyung is a high cultural value building, and asking the Government to ignore it will have a negative impact on the City of Batusangkar.Keywords: Management, Istano Basa Pagaruyung, Tourism Object